Acute chest pain: Acute coronary syndrome versus lead perforation: A case report - Peddi, Prashanth (BioMed Central, 2010)
BACKGROUND: Diagnosing pacemaker lead perforation in the setting of chest pain and EKG changes is difficult and usually not considered unless we have awareness and high index of suspicion. This kind of clinical scenario represents one of the diagnostic challenges. CASE PRESENTATION: A 77 year-old Caucasian female came to emergency room with left sided non-exertional chest pain radiating to her back for the past two days. A week prior to this presentation, she had a stent supported angioplasty for in-stent re-stenosis and subsequently dual chamber pacemaker implantation for sick sinus syndrome. On physical exam she is very obese, had normal vital signs, peripheral pulses and cardio-respiratory exam. Electrocardiogram revealed new T- wave inversions in inferior and anterior leads. Initial chest X-ray, 2D-Echocardiogram and cardiac enzymes were normal. Acute coronary syndrome was considered as an initial probable diagnosis. She was anticoagulated with heparin and eptifibatide. Patient continued to have chest pain with negative cardiac biomarkers. She developed hypotension, oliguria, elevated white count, pyuria and renal failure. Because of a normal 2D-echocardiogram, cardiac etiology for shock was not suspected. After initial fluid challenge, empiric treatment for septic shock was initiated with antibiotics and vasopressors. Work up for pulmonary embolism and intra-abdominal hemorrhage was negative. Because of persistent chest pain, shock with cold & clammy extremities and elevated central venous pressure cardiogenic shock was considered and a repeat 2D-echocardiogram was done on third day of hospitalization which revealed pericardial effusion. Non-contrast CT-scan chest done to look for lead position confirmed that she had hemorrhagic pericardial effusion along with lead perforation. Patient underwent pericardial window placement along with over-sewing of atrial wall to seal the leakage point. The patient improved and was then discharged from the hospital. CONCLUSION: Lead perforation presenting with chest pain and EKG changes is often not appreciated resulting in significant delay in diagnosis and inappropriate treatment.